Towards zero-defect manufacturing: A proactive quality risk assessment of welding imperfections in wind tower production - Yusraini Muharni; Evi Febianti; Muhammad Adha Ilhami; Ade Irman Saeful Muttaqien; Lely Herlina; Muhammad Rafi Hasyim; Anting Wulandari; Kulsum Kulsum; Hartono Hartono; Maria Ulfah (Universitas Sultan Ageng Tirtayasa, 2026)
Wind tower manufacturing demands exceptionally high-quality standards due to its critical role in renewable energy infrastructure. However, defect occurrences during the production process remain a persistent challenge that can compromise structural integrity, increase rework costs, and delay project delivery. This study aims to identify, analyse, and evaluate the risk of defects in the wind tower production process by using an integrated approach of 5 Whys and Failure Mode and Effects Analysis (FMEA). The 5 Whys methodology was employed to trace the root causes of recurring defects, while FMEA was utilized to assess failure modes based on severity, occurrence, and detectability values, resulting in a Risk Priority Number (RPN) for each identified failure. The 5 Whys analysis revealed that the root of the problem lies in the absence of a procedure for verifying work positions before welding. The improvements focused on the design the standard operating procedure, increasing operator competency, controlling process parameters, and validation through trials and inspections to support a decrease in the level of defects and improve product quality.